Development of Alert Radiation Monitoring System - Johari, Aina Athirah; Mohamad, Elmy Johana (Evolution in Electrical and Electronic Engineering, 2022)
At the moment, radiation workers still maintain use survey meters to read the level of radiation in a place or place where they work. Users of survey meters that are relatively heavy and not user-friendly require employees or users to be sensitive to radiation readings around them. this study has been done to help radiation workers be more sensitive to radiation readings more easily in the workplace to avoid self-harming incidents by providing a warning system. The method used to perform the study was by connecting the detector, Arduino radiation detector compatibility kit, battery, and ESP8266 NodeMCU with the Blynk web application. The study was conducted for 3 days at the Malaysian Nuclear Agency and proved that the system works well and was able to read the background level of radiation in the workplace. This study successfully met all the stated objectives.